Parallax: Shahzia Sikander - Sikander, Shahzia (Tufts University Art Galleries, 2018)
Exhibition catalog, 10 Sept-6 Dec 2015. Contributions: Ayesha Jalal, Amy Ingrid Schlegel, Tasneem Zehra Husain, Sara Raza. SB11 project
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Pakistan